KARAKTERISTIK KEFIR SUSU SAPI DENGAN INOKULUM RAGI TAPE - Sinurat, Rosmaida La; Ekowati, Christina Nugroho; Sumardi, Sumardi; Farisi, Salman (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
Kefir is a fermented milk product that has the typical flavours (acids and alcohol) and its processed by a number of microbes which include lactic acid bacteria (LAB) and yeasts.The aims of this study were to know the character of the population of lactic acid bacteria (LAB), a population of yeasts, and chemical characters among others total acid, pH and alcohol levels in kefir milk with inoculum ragi tape. The population of LAB and the population of yeast were calculated with the method of calculation of Total Plate Count. The levels of total acid titration method were determined by the acid. Acidity was measured using a pH meter and alcohol levels were determined by the method of Conway Micro Diffusion. The results showed that the number of LAB has increased to 24 hour fermentations of 9.01 log cells/ml (1,1x109 cells/ml), then the number of cells did not change much until the fermentation time was 48 hours and 72 hours of fermentation on the decline of 8.07 log cells /ml (1,2x108 cells/ml) while the yeast experiences increased from 6 hours to 24 hours, then the amount of yeast did not much change from the 24 to 72 hours of the highest number of yeasts during fermentation 48 hours an amount of 6.12 log cells /ml (1,3x106 cells/ml) and the amount of yeasts did not decline at the time of 72 hours. Total acid continued to experience increased with the number of 0.38-1.24%, pH continued to decline from 6,47-4.27 and alcohol levels continued to experience increased with the number of 0.05-0.38% b/v. Keywords: Inoculum, Kefir Milk, Lactic Acid Bacteria, Ragi Tape, Yeast